Reflexive practice learning as the potential to become a competent future practitioner - Kodele, Tadeja (CEPS journal, 2023)
The article presents an example of social work education, in which reflexive practice learning was used to help students work competently in professional practice. Within an action research project, new forms of mentoring support for students working with families facing multiple challenges were developed as part of their practice learning. This paper presents the results of a qualitative analysis of the students’ reflections on mentoring meetings. Content analysis was used for data analysis. The analysis shows that practice learning should be framed as a reflexive dialogue between mentors and students. Students need opportunities to share experiences and expand their knowledge with other students in small mentoring groups. The continuous and concrete support that the mentoring group provided to the students in practice enabled them to deal with the sense of uncertainty that often arises in collaborative processes of help.
Keywords: mentoring; mentorstvo; practice learning; praktično učenje; refleksivni pristop; reflexive approach; social work; socialno delo